2021
DOI: 10.1055/s-0041-1729781
|View full text |Cite
|
Sign up to set email alerts
|

Role of ACE 2 and Vitamin D: The Two Players in Global Fight against COVID-19 Pandemic

Abstract: The global pandemic of coronavirus disease 2019 (COVID-19) has spread across the borders, gaining attention from both health care professional and researchers to understand the mode of entry and actions induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), its causative agent in the human body. The role of angiotensin-converting enzyme–2 (ACE2) in facilitating the entry of the virus in the host cell by binding to it is similar to SARS-CoV-1, the causative agent for severe acute respiratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…Regarding symptoms, the WHO adds: “While common symptoms of long COVID can include fatigue, shortness of breath, and cognitive dysfunction over 200 different symptoms have been reported that can have an impact on everyday functioning”. 9 Although several treatments have been established for COVID-19 and more are under development, 10 , 11 , 12 , 13 , 14 , 15 , 16 there is still no treatment for long COVID. 9 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Regarding symptoms, the WHO adds: “While common symptoms of long COVID can include fatigue, shortness of breath, and cognitive dysfunction over 200 different symptoms have been reported that can have an impact on everyday functioning”. 9 Although several treatments have been established for COVID-19 and more are under development, 10 , 11 , 12 , 13 , 14 , 15 , 16 there is still no treatment for long COVID. 9 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%